Strategi Bersaing Pt Xyz Dalam Bisnis Spbg - Grace Theresia Widyani dan Chairy (Universitas Tarumanagara, 2019)
This study aims to analyze and define competitive strategy for PT XYZ. PT XYZ is a company engaged in the field of natural gas energy supply through Gas Fuel Filling Station (SPBG). The gas fuel sold through SPBG is natural gas in the form of Compressed Natural Gas (CNG). CNG is an environmentally friendly gas. Its price is cheaper than fuel oil (BBM). Along with the incessant government to promote the use of gas fuel (BBG) in the form of CNG - as a substitute for BBM, and more competitive BBG price to BBM, it creates considerable opportunities for the Company to grow its business. However, the Company also encountered obstacles, such as the price of BBG to consumers in the transportation sector is standardized by the Government, and still, the least number of existing SPBG nowadays, resulting in not many consumers of the transportation sector are interested to switch to BBG. The author made a list of all matters related to the SPBG business by using management theories, ie, inventorying all constraints in the external environment and the internal environment of the SPBG business. The results of the inventory then, set out in the SWOT table. Moreover, from the SWOT table, the analysis is done with EFE IFE IE Matrix. At the end, it can be concluded that the SPBG business position is in column V in IE Matrix, which is held (hold and maintain). The right competitive strategy for the Company is market penetration and product development strategy.